Function and clinical application of exosome—how to improve tumor immunotherapy? - Qin, Siwen; Cao, Jilong; Ma, Xiaoxue (Frontiers in Cell and Developmental Biology, 2023)
In recent years, immunotherapy has been increasingly used in clinical practice to treat tumors. However, immunotherapy's efficacy varies between tumor types and patient populations, and long-term drug resistance often occurs during treatment.Therefore, it is essential to explore the molecular mechanisms of immunotherapy to improve its efficacy. In this review, we focus on the significance of tumor-derived exosomes in the clinical treatment of tumors and how modifying these exosomes may enhance immune effectiveness. Specifically, we discuss exosome components, such as RNA, lipids, and proteins, and the role of membrane molecules on exosome surfaces.Additionally, we highlight the importance of engineered exosomes for tumor immunotherapy. Our goal is to propose new strategies to improve the efficacy of tumor immunotherapy.